The financial performance of selected REITs from S&P500 - Cicmil, Danica (Anali Ekonomskog fakulteta u Subotici, 2023)
Every investor, trader, portfolio manager or analyst tries to evaluate the performance of the selected asset to develop a strategy for investment or trading. There are a variety of analyses that can be used depending on the asset class chosen. Since this paper is about REITs (Real Estate Investment Trusts), two ratios will be calculated: DPU (dividend distribution per unit) and FFO (funds from operations). The objective is to investigate whether these two performance measures produced significantly different results during the COVID 19 crisis. The selected assets were chosen to cover most of the asset classes in the real estate industry: 1. Public Storage: PSA, 2. Host Hotels & Resorts: HST, 3. Healthpeak Properties: Peak, 4. AIMCO: AIV. It can be concluded that REITs as an asset class generally offer steady returns, however, some sectors are more affected than others during the crisis. It is difficult to estimate which sector will be affected, as crises are always novelties. The best performing asset class was that of the storage sector, which remained stable and positive throughout the entire period, paying higher dividends than the other asset classes.